Electricity infrastructure vulnerabilities due to long-term growth and extreme heat from climate change in Los Angeles County. (May 2019) - Burillo, Daniel; Chester, Mikhail V.; Pincetl, Stephanie; Fournier, Eric
Abstract: Many studies have estimated the effects of rising air temperatures due to climate change on electricity infrastructure systems, but none have quantified impacts in terms of potential outages down to the neighborhood scale. Using high-resolution climate projections, infrastructure maps, and forecasts of peak electricity demand for Los Angeles County (LAC), we estimated vulnerabilities in the electricity infrastructure to 2060. We considered rising air temperatures under IPCC RCP 4.5 and RCP 8.5 at 2 km 2 grid cell resolution, two local government population growth scenarios, different efficiency implementations of new residential and commercial buildings, air conditioners (AC), and higher AC penetration. Results were that generators, substations, and transmission lines could lose up to 20% of safe operating capacities (MW). Moreover, based on recent historical load factors for substations in the Southern California Edison service territory, 848–6, 724 MW (4–32%) of additional capacity, distributed energy resources, and/or peak load shifting could be needed by 2060 to avoid hardware overloading and outages. If peak load is not mitigated, and/or additional infrastructure capacity not added, then all scenarios result in > 100% substation overloading in Santa Clarita, which would trigger automatic outages, and > 20% substation overloading in at least Lancaster, Palmdale, and Pomona in which protection gear could trip outages within 30 min. Several climate change adaptation options are discussed for electricity infrastructure and building stock with consideration for trade-offs in system stability and other energy and environmental goals. Highlights: Components are vulnerable to rising air temperatures by 2–20% of capacity by 2060. Only Santa Monica Bay area is not vulnerable to temperatures above 40 °C (104 °F). Population growth and technology affect peak demand more than temperature rise. Santa Clarita, Lancaster, Palmdale, and Pomona at highest risk of outages. Need 848–6724 MW (4–32%) of new substation capacity, DER, or load shifting.